Gambaran Status Gizi Ibu Hamil di PMB Ny. Ika Desa Siasem Kecamatan Wanasari Kabupaten Brebes Tahun 2019 - Dea Riskha Fitriliana (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2020)
This study aims to get a clear description on the nutritional status of pregnant women in PMB Siasem, Wanasari District, Brebes Regency. This research method is descriptive research. The population is 25 people. All family members used as research subjects. The results of the study were obtained by high economic families by 40% and low economic families by 60% while pregnant women with good nutritional status were 72% and pregnant women with poor nutritional status were 28%. It can be concluded that there is a very significant picture between age, family understanding, education level with the nutritional status of pregnant women in PMB Siasem, Wanasari District, Brebes Regency.